A comparison of genetic variants between proficient low- and high-risk sport participants - Thomson, C. J.; Power, R. J.; Carlson, S. R.; Rupert, J. L.; Michel, G. (Journal of Sports Sciences, 2015)
Athletes participating in high-risk sports consistently report higher scores on sensation-seeking measures than do low-risk athletes or non-athletic controls. To determine whether genetic variants commonly associated with sensation seeking were over-represented in such athletes, proficient practitioners of high-risk (n = 141) and low-risk sports (n = 132) were compared for scores on sensation seeking and then genotyped at 33 polymorphic loci in 14 candidate genes. As expected, athletes participating in high-risk sports score higher on sensation seeking than did low-risk sport athletes (P < .01). Genotypes were associated with high-risk sport participation for two genes (stathmin, (P = .004) and brain-derived neurotrophic factor (P = .03)) as well as when demographically matched subsets of the sport cohorts were compared (P < .05); however, in all cases, associations did not survive correction for multiple testing.